Pengaruh penggunaan pupuk daun “Organik” terhadap produktivitas dan kualitas rumput gajah (Pennisetum purpureum CV. Hawai) sebagai hijauan pakan - Badat Muwakhid; Usman Ali (Universitas Sebelas Maret, 2021)
Objective: Elephant grass is a forage that is commonly used as feed. The growth of elephant grass can be supported by applying appropriate fertilizers. The purpose of this study was to determine the appropriate level of